2019
DOI: 10.1002/joc.6060
|View full text |Cite
|
Sign up to set email alerts
|

Attribution analysis of actual and potential evapotranspiration changes based on the complementary relationship theory in the Huai River basin of eastern China

Abstract: Accurate terrestrial evapotranspiration (ET) estimation and understanding the causes of ET variation are essential for water resource management and irrigation planning. In this research, the complementary relationship (CR) between actual evapotranspiration (ET a ) and potential evapotranspiration (ET p ) was evaluated. An Advection-Aridity (AA) model was calibrated and validated using eddy covariance measurements. The spatiotemporal variations of ET a , ET p and associated meteorological variables were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 97 publications
1
9
0
Order By: Relevance
“…Sonmez and Kale used the Pettitt analysis to determine that the hydrometeorological elements of the Filyos River (Turkey) experienced abrupt changes in approximately 2000 [49]. Chu et al used the MK test and the Theil-Sen estimate to determine that the abrupt change point of ET 0 in the Huaihe River Basin was approximately 1990 [50]. Wang et al used the MK test and the Pettitt test change-point statistics to find that the hydrometeorological elements of the Taihang Mountain area changed abruptly in approximately 1982 [51].…”
Section: Introductionmentioning
confidence: 99%
“…Sonmez and Kale used the Pettitt analysis to determine that the hydrometeorological elements of the Filyos River (Turkey) experienced abrupt changes in approximately 2000 [49]. Chu et al used the MK test and the Theil-Sen estimate to determine that the abrupt change point of ET 0 in the Huaihe River Basin was approximately 1990 [50]. Wang et al used the MK test and the Pettitt test change-point statistics to find that the hydrometeorological elements of the Taihang Mountain area changed abruptly in approximately 1982 [51].…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the variation of AI more concretely in northern China, Zhang et al [63] used 283 standard meteorological stations to analyze the spatiotemporal variations of AI and its influencing factors. It was found that the AI decreased significantly and the dry and wet areas increased and decreased, respectively, on the east and west sides of 100 • E, and the duration of sunshine and Pre were the main dominant factors in the declining AI trend [33]. Unlike in the study of Zhao et al [60], the AI calculated by the ratio of Pre to ET 0 exhibited a downward trend in the Loess Plateau and the boundary of dry land region was expanded there [64], and Pre was the main cause of AI variations.…”
Section: Discussionmentioning
confidence: 95%
“…During the half past century, waterlogged areas were widespread, accompanied by a prominent conflict between humans and water or land. Against the historical background, both the disordered Huai River water system and the deteriorated environment have aggravated the frequent occurrence of extreme events such as floods and droughts [33,42].…”
Section: Study Area and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, temperatures display a gradual increase with an annual average of 11 °C in the north to 16 °C in the south. Alternatively, the mean annual potential evapotranspiration is estimated to be between 950 and 1,150 mm using the Penman method (Chu et al 2019). In comparison, the annual average runoff depth is approximated to be 231 mm, predominantly occurring in the flood season (Song et al 2015).…”
Section: Methodology Study Areamentioning
confidence: 99%